Analysis of Karaikal winds with special reference to installation of windmills - ALBEEZ, S. A. H. (MAUSAM, 1983)
Due to energy crisis it has become a necessity for the world to think of different sources of energy besides oil as fuel. In a developing country like India where oil bill is increasing every year, it is felt that, an alternate and cheap source of power would be from windmill, particularly, at places where winds are strong for long periods. Proper planning for selection of site and design of windmills is essential. It is with this view that the surface wind data at Karaikal was analysed. In this paper, a frequency analysis of three hourly values of winds recorded by cup type anemometer at Karaikal during the five year period 1975-1979 is made. The frequency distribution of three hourly values of winds in four ranges, viz., 0-9 kmph, 10-15 kmph, 16-19 kmph and 20 kmph and above has been determined. Monthwise frequency distribution is also presented.